2016
DOI: 10.1039/c6sc00305b
|View full text |Cite
|
Sign up to set email alerts
|

Tetrathiafulvalene-containing polymers for simultaneous non-covalent modification and electronic modulation of MoS2 nanomaterials

Abstract: Polymers with pendent tetrathiafulvalene groups for solubilization and electronic modification of MoS2 nanosheets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 41 publications
2
47
1
1
Order By: Relevance
“…3), in accordance with the literature reports. 40,56 These phenomena indicate that the monolayer g-C 3 N 4 may be tuned into p/n-type materials by doping with the electron-withdrawing/donating TCNQ and TTF molecules.…”
Section: Resultsmentioning
confidence: 97%
“…3), in accordance with the literature reports. 40,56 These phenomena indicate that the monolayer g-C 3 N 4 may be tuned into p/n-type materials by doping with the electron-withdrawing/donating TCNQ and TTF molecules.…”
Section: Resultsmentioning
confidence: 97%
“…22 The effects of organic molecules adsorption such as TCNQ, TCNE, TTF, BV, F4TCNQ, and benzene on the electronic and optical properties of the monolayer MoS 2 have been studied in the literature. [23][24][25][26] A reduction of the bandgap was found due to the existence of the at molecular levels of the organic molecules in the bandgap region of the monolayer MoS 2 . The theoretical study showed that the adsorption of TCNQ signicantly enhances the peak height of the optical absorption of the monolayer MoS 2 in the infrared region of the spectrum.…”
Section: Introductionmentioning
confidence: 98%
“…Therefore, the Mo atoms at the S vacancies were exposed, which could function as the coordination centers to bond with ligands, as shown in Figure a. With this strategy, various kinds of building blocks that involved sulfur‐, oxygen‐, nitrogen‐containing functional groups were employed as ligands to coordinate with MoS 2 through S vacancies, resulting in multifunctional hybrid nanostructures …”
Section: Coordination‐driven Assembly Based On Tmdsmentioning
confidence: 99%
“…In addition to the thiol terminated building blocks, disulfide‐containing functional groups could also coordinate with the Mo atoms at the S vacancies, as illustrated in Figure a. Both small molecules and macromolecules that involved disulfide bonds were proposed to hybridize with MoS 2 through coordination reactions . Similar to the S atoms, the O and N atoms also contained lone pair electrons.…”
Section: Coordination‐driven Assembly Based On Tmdsmentioning
confidence: 99%